IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 4 TAHUN 2018 PASAL 1 AYAT 6 TENTANG PEMUNGUTAN PAJAK KOS DI KECAMATAN TEMBALANG - Kharisma Lufiana; Nina Widowati (Journal of Public Policy and Management Review, 2020)
Boarding tax is a levy that is levied on the operation of rented houses with more than 10 (ten) rooms. The existence of the tax is expected to be able to increase regional revenue so that it has an impact on increasing Local Revenue (PAD). In reality, there are still taxpayers whose boarding houses are not listed as tax objects, this is the background of this research. This policy is stated in Semarang City Regulation Number 4 of 2018 Article 1 Paragraph 6 About Hotel Taxes. The purpose of this research is to describe how the implementation of Semarang City Regional Regulation number 4 of 2018 article 1 paragraph 6 regarding boarding tax in the District of Tembalang and determine the inhibiting factors of implementation. The theory used is theory 5 (five) accuracy of the implementation of Riant Nugroho and Van Meter Van Horn with standard and target variables, and social conditions. This research is a descriptive qualitative research. Data collection techniques using interviews and documentation. The selection of informants uses accidental sampling. The results showed that the implementation of the kos tax collection policy in Tembalang sub-district was still not running as expected from the policy, target and process accuracy. The inhibiting factors for the implementation of the kos tax collection policy are unclear standards and targets and social conditions for the community's response to the existence of these policies, which accept and reject them. Recommendations that can be given are finding or formulating the implementation of the tax tax policy, increasing the provision of understanding of the tax policy for the public, especially taxpayers.